# Simplify the quantity {(x + 6)/12}/{(x - 8)/10}.

**Solution:**

Given: Expression is {(x + 6)/12}/{(x - 8)/10}

It can be written as

= (x + 6)/12 × 10/(x - 8)

By taking 2 common in both numerator and denominator

= [(x + 6)/ 2(6)] × [2(5)/ (x - 8)]

By further simplification

= (x + 6)/6 × 5/(x - 8)

So we get,

= 5(x + 6)/6(x - 8)

Therefore, by simplifying the quantity we get 5(x + 6)/6(x - 8).

## Simplify the quantity {(x + 6)/12}/{(x - 8)/10}.

**Summary:**

Simplifying the quantity {(x + 6)/12}/{(x - 8)/10} we get 5(x + 6)/6(x - 8).